HAMBATAN KOMUNIKASI ORGANISASI KARANG TARUNA DUSUN MALANGAN DESA KEPATIHAN KABUPATEN WONOGIRI - Endra Aji Saputra; Sihabuddin Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
Karang Taruna is a village-based youth organization that plays a vital role in shaping character and enhancing social awareness among young people. However, in practice, internal communication barriers often arise, leading to low member participation. This issue is also evident in Karang Taruna Dusun Malangan, Kepatihan Village, Wonogiri, where miscommunication occurs in coordination and decision-making processes. This study applies the theory of organizational communication barriers by Ummah, as outlined in Komunikasi Organisasi, which defines communication as a message exchange process within a network of interdependent relationships aimed at managing uncertainty and change. The research aims to identify communication barriers within the organization of Karang Taruna Dusun Malangan. Using a descriptive qualitative method with interviews and documentation, the study reveals that the main communication barriers include psychological barriers, such as lack of confidence and fear of expressing opinions; cognitive barriers due to differing viewpoints and limited open discussion; and status-related barriers arising from differences in roles and levels of member engagement. Physical and socio-cultural barriers were found to be insignificant due to members’ similar backgrounds and close geographic proximity. These findings highlight the importance of building a more open, inclusive, and effective communication model to improve participation and ensure the sustainability of Karang Taruna as a youth organization at the village level. Keywords: organization communication, communication barriers, karang taruna, youth organization.